Transition voltages respond to synthetic reorientation of embedded dipoles in self-assembled monolayers. Issue 1 (5th November 2015) - Kovalchuk, Andrii; Abu-Husein, Tarek; Fracasso, Davide; Egger, David A.; Zojer, Egbert; Zharnikov, Michael; Terfort, Andreas; Chiechi, Ryan C.
Abstract : Transition voltages respond to the collective action of dipole moments embedded in self-assembled monolayers. Abstract : We studied the influence of embedded dipole moments in self-assembled monolayers (SAMs) formed on template stripped Au surfaces with liquid eutectic Ga–In alloy as a top electrode. We designed three molecules based on a p -terphenyl structure in which the central aromatic ring is either phenyl or a dipole-inducing pyrimidyl in one of two different orientations. All three form well defined SAMs with similar thickness, packing density and tilt angle, with dipole moments embedded in the SAM, isolated from either interface. The magnitude of the current density is dominated by the tunneling distance and is not affected by the presence of dipole moments; however, transition voltages ( V T ) show a clear linear correlation with the shift in the work function of Au induced by the collective action of the embedded dipoles. This observation demonstrates that V T can be manipulated synthetically, without altering either the interfaces or electrodes and that trends in V T can be related to experimental observables on the SAMs before installing the top contact. Calculated projected density of states of the SAMs on Au surfaces that relate HOMO-derived states to V T further show that energy level alignment within an assembled junction can be predicted and adjusted by embedding dipoles in a SAM without altering any other properties of the junction. We therefore suggest that trends in V T can be used analogously to β in systems for which length-dependence is physically or experimentally inaccessible.